Fire-resistant composites based on acrylic-functionalized lignin and polyester resin obtained from waste poly(ethylene terephthalate) - Knežević Nataša; Jovanović Aleksandar; Bošnjaković Jovan; Milošević Milena; Rančić Milica; Marinković Aleksandar; Gržetić Jelena; Gamoudi Houda (Scientific Technical Review, 2022)
This paper investigates the using potential of acryl-functionalized kraft lignin (AKL) in reducing the flammability of polymer composites based on recycled unsaturated polyester resins (UPR). Acryl functionalization of kraft lignin was performed by direct esterification of free polyphenolic groups with acryloyl chloride, after what, the AKL was blended in UPR resin synthesized from the polyols obtained by catalytic depolymerization of waste poly(ethylene terephthalate). The AKL was homogenized in UPR resin in different weight ratios: 2.5, 5.0, 7.5, and 12.5 wt.%. Structural and dynamic-mechanical characteristics of acryl-functionalized kraft lignin and composites were determined using FTIR spectroscopy, dynamicmechanical analysis (DMA), and tensile tests. The influence of functionalization and mass fraction of AKL on tensile and thermal properties of UPR resin was studied. The thermal properties of the composite were tested according to the standard UL-94 method, based on which the highest category of heat-resistant materials is a composite with 12.5 wt.% acylfunctionalized lignin.